Pengaruh Konflik Pemerintah Sipil dan Militer Myanmar terhadap Kebijakan Myanmar dalam Penanganan Kasus Rohingya tahun 2015-2019 - Normawati Susanto; Tri Cahyo Utomo (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Rohingya is a minority ethnic in Myanmar that has been discriminated since the reign of the military junta (tatmadaw). In the era of Aung San Suu Kyi which the Rohingya crisis has not handled well, places Myanmar in a difficult position internationally. In the domestic sphere, conflict between the civilian government and tatmadaw related to Rohingya handling policies occured because the position of tatmadaw in politics remains strong, as stipulated in the 2008 Myanmar Constitution. This study discusses how the conflict influences Myanmar policies towards the handling of Rohingya crisis. The civilian government formed an Advisory Commission on Rakhine State to handle the case, while the tatmadaw carried out a clearance operation in handling it which caused instability in Myanmar. This study will use a decision-making model on bureaucratic politics by Graham T. Allison to analyze how the conflict within Myanmar government influences Rohingya policies by looking at two contested actors, tatmadaw and civilian government. This research uses qualitative and descriptive methods by using literature study in data collection. The result of this study shows the fact that the conflict between the civilian government and tatmadaw of Myanmar has been detaining the process of handling Rohingya case.